A constituição do Orientador Pedagógico: entre saberes e fazeres da profissão - Oliveira, Priscila Borges Ribeiro (Universidade Federal de São Carlos, 2023)
This research focused on the search to understand the constitution of the Pedagogical Advisor in the Municipal Network of Sorocaba, as historical subjects in everyday school life, with specific and distinct function of the teacher, considered from two links of the profession: the knowing and the doing. The qualitative and interpretative approach problematizes the field tilting the look at the gaps and the distances between theory and practice, the needs of reality and the relationship between the elements of professional development of these subjects. The theoretical pillars are based on: Placco and Almeida (2015), Placco, Souza and Almeida (2012), conceptualizing this professional as a mediator who directs actions, aiming to transform school actions, aware that his work is not done in isolation, but collectively and in Tardif (2002) which sustains us on the concept of knowledge, as a basis for action and professional training. As a methodological instrument to analyze and interpret the data, we opted for Data Triangulation, built in its complexity, depth and diversity, organized in descriptive and analytical chapters, built from three methodological instruments: the Documentary Study, collating the documents produced by the municipal network, the documents and the laws that cross the knowledge and the training and professional development and the Conversation Wheel ending the methodological process, in a dialogic, meaningful movement, full of reflection and emotion, providing time and voice to participants, beginners and experienced professionals, different types of education. Intertwined in the daily pedagogical performance of the Pedagogical Advisor, we consider the links (knowledge and actions), from the understanding of reality and analysis of the data together with the results and the Consider-Actions, intend to present tessituras on the constitution of the Pedagogical Advisor, considering the knowledge and the doings, as well as elucidate possible contributions to the expansion of knowledge of the field, highlighting the inferences, possibilities that can favor the professional constitution, with regard to guiding, coordinating, articulating, forming and transforming. The production translates the search for answers, alongside the academic and social relevance, starting from the assumptions and the standpoint, revealing experiences and experiences along the trajectory of the researcher as a Pedagogical and professional advisor of education in the public network of Sorocaba. As an artistic-literary device during the course of this production, excerpts, and moments recorded in Cordel’s Literature, the result of reading, re-reading, revisiting and re-signification of the researcher’s 'Memoriel', while looking at the understanding of this professional constitution, knowledge and doing, intertwine and generate new ones, building shortcuts, shortening distances, trimming edges and reducing gaps, the commonplace of these professionals.
The constitution of the pedagogical advisor: between knowledge and the profession
Keywords: Orientador-pedagógico; Saberes e fazeres; Desenvolvimento profissional; Pedagogical advisor; Knowledge and doing; Professional development; CIENCIAS HUMANAS::EDUCACAO